On The Inverse Function Theorem and its Generalization in the Unitary Space: On The Inverse Function Theorem and its Generalization in the Unitary Space - Eziokwu, Chigozie Emmanuel (Asian Journal of Mathematical Sciences(AJMS), 2020)
It is obvious that the inverse function theorem holds in the Banach space for R . In my paper on the generalized inverse function theorem, it was observed that the inverse function theorem also holds for Rn . However, in this paper, I attempted to establish that it holds in the unitary space and consequently can be extended to Cn ; the generalized unitary space.